2011
DOI: 10.1007/s10337-011-2092-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Mobile Phase Condition on Chiral Recognition of Poly(l-phenylalanine) Chiral Stationary Phase

Abstract: Characteristic of chiral stationary phase (CSP) with poly(L-phenylalanine) peptide selector, which is in -helical state, was reported. Since environmental factors affect peptide conformation, the changes of enantioselectivity were examined depending on column temperature and mobile phase conditions (ionic strength, pH, mobile phase composition). Column temperature and pH drastically affected the enantioselectivity.Based on these changes, the relation between chiral recognition and secondary structure of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…With the addition of L-leucine, L-proline, L-phe, or N,N-dimethyl-L-phenylalanine, many enantiomers and derivatized amino acids, such as tryptophan, phenylalanine, warfarin, and valine, have been successfully resolutioned [15][16][17][18]. Considering that DMMD was an analogue of amine acid, the diastereomeric mixed-ligand complexes containing amino acide, bivalence copper, and DMMD could be formed by their carboxylic group and neighboring amino group, which resulted in the cis-and trans-configurations.…”
Section: Resultsmentioning
confidence: 99%
“…With the addition of L-leucine, L-proline, L-phe, or N,N-dimethyl-L-phenylalanine, many enantiomers and derivatized amino acids, such as tryptophan, phenylalanine, warfarin, and valine, have been successfully resolutioned [15][16][17][18]. Considering that DMMD was an analogue of amine acid, the diastereomeric mixed-ligand complexes containing amino acide, bivalence copper, and DMMD could be formed by their carboxylic group and neighboring amino group, which resulted in the cis-and trans-configurations.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Chen used poly(N-benzyl-L-glutamine)-coated silica for the chiral separation of hydantoins [35]. We developed a novel CSP with phenylalanine (Phe) peptide as chiral selector [36][37][38]. The CSP was prepared on APS by solid-phase synthesis with tert-butoxycarbonyl (Boc) amino acids.…”
Section: Preparation and Characterization Of Poly(l-phenylalanine) Chmentioning
confidence: 99%
“…Nowadays, a large diversity of CSPs is available to carry out enantioselective resolution. These CSPs mainly involve compounds such as cyclodextrins, polysaccharides, proteins, or peptide oligomers. In the latter case, previous studies suggested that specific secondary structures, such as a helical conformation, can promote and enhance enantioselectivity. In 2011, Wu et al investigated peptoids as a new class of chiral selector compounds in stationary phases . Peptoids are peptidomimetic molecules in which the side chain is appended to the nitrogen atom of the amide group instead of the carbon in the α-position to the amide carbonyl as it is the case in peptides .…”
Section: Introductionmentioning
confidence: 99%